Burden of caregivers of dementia patients and affecting factors in Turkey: A Systematic Review - Adana, Filiz; Safiye Ozvurmaz; Aliye Mandiracioglu (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the burden on the caregivers of dementia patients and the factors affecting the perception of it. Methods: The current systematic review was done in Turkey and comprised a search between October 2019 and March 2020 on Turkish and English indexes, including the Turkish Academic Network and Information Center database, Web of Science, PubMed, Education Resources Information Centre, Medline, SocINDEX, Cumulative Index to Nursing and Allied Health Literature, PsycINFO, Google Scholar, Ulusal Tez Merkezi, Dergipark and Turk Medline. The key words used were ‘Demans’, ‘alzheimer’, ‘bak?m verenler’, ‘hastal?k yükü’, ‘dementia’, ‘alzheimer's’, ‘caregivers’ and ‘burden of illness’. Studies included were those having been conducted from 2010 to 2019 and which used the Personal Information Form, the Zarit Caregiver Burden Scale and the Caregiver Burden Inventory. Results: Of the 4,182 studies initially found, 502(12%) were accessed using Turkish key words, and 3,680(88%) using English key words. Overall, 16(0.38%) studies met the inclusion criteria and were reviewed. There were 2,060 caregivers and 414 patients in these studies. A high number of variables affected caregiver burden. Patient-related variables reported in multiple studies included time spent on caregiving, dementia stage, patient's age and level of patient's dependence. Conclusion: The most frequently reported caregiver-related variables which increased caregiver burden were being female, younger age, being unemployed, older age, lower education level. Key Words: Dementia, Alzheimer's, Caregivers, Burden of illness. Continuous...